The prospects for rainwater harvesting at the University of Cape Town - Lepota, Tsepiso (Department of Civil Engineering, 2026)
Water is a necessity for sustaining life and important for all daily activities. South Africa (SA) has, over the years, faced several challenges concerning the lack of water. The lack of water can have detrimental effects on the well-being of people and the ecosystem, and this was evident when the lives of the people of Cape Town were impacted because of a three-year drought between 2015 and 2018. This amplified the need for resilient and adaptive water infrastructure and water services and water sensitivity from all users. In 2020 the University of Cape Town (UCT) called for projects that address environmental, social, and financial sustainability on its campuses as part of its mission to contribute to sustainability, resilience, and water sensitivity. Transitioning towards sustainable water management (SWM) has been proposed as a pathway to reducing the current municipal water demand of the university. This research thus investigated benefits such as water and economic savings that UCT might derive from implementing rainwater harvesting (RWH) on the campuses to reduce dependence on imported (municipal) water treated to unnecessarily high standards for non-potable purposes like toilet-flushing. Representative buildings on the Upper Campus (Fuller Hall, Snape, New Engineering Building (NEB) and Hlanganani) and Middle Campus (Woolsack and Masingene) of UCT, a high-level parking area (P18), and the tennis court on Upper Campus were identified as potential catchment areas that were investigated for RWH. The results for Woolsack were then generalised to other universities across SA to investigate the impact of varying rainfall patterns on the implementation of RWH systems. The study used the ‘Yield after spillage' (YAS) algorithm in a Microsoft Excel spreadsheet to identify the relationship between water demand, supply, and storage for RWH. Various storage sizes from 10 kL to 1000 kL were assessed. The economic costs of the RWH systems were limited to the cost of storage, which was then multiplied by arbitrary factors to cater for other potential capital and operating expenditures. The cost savings from harvested rainwater were estimated using the City of Cape Town (CoCT) 2021/2022 tariffs for Level 1 and Emergency response water restrictions. A 20-year discount period and a 4% interest rate were used to determine the capital recovery amounts of the cost of ownership of the RWH systems. A Multi-Criteria Analysis (MCA) tool that considered three weighting scenarios of the harvestable rainfall and economic viability based on the benefit-cost ratio (BCR) (0.5/0.5, 0.6/0.4 and 0.4/0.6) was used to identify the most promising RWH system. It was found that student residences (Fuller Hall and Woolsack) could potentially reap the greatest benefits from installing RWH systems due to a better balance between the supply from the roofs and the related water demand than other university buildings. Approximately 4900 kL and 4000 kL of rainwater can be harvested from Woolsack and Fuller Hall respectively in a year if 100 kL tanks were provided. The cost savings from the yield were estimated at R43,400/year and R56,300/year for the same tank size. The integration of the P18 parking lot and the nearby tennis court into one catchment had the biggest economic savings due to the large quantity of rainwater that can be collected to replace municipal water but the cost of installation of all the P18 systems was very expensive when the cost of the sand filter to treat the dirty water from P18 was included. As a result, the tennis court catchment without P18 was identified as the most promising catchment instead. Approximately 7,500 kL of rainwater could be harvested if 1000 kL tanks were provided, while the potential cost savings associated with the yield were estimated at R316,800/year when the rainwater from the tennis court catchment is supplied to all Upper Campus buildings. It was also concluded that UCT is in a relatively good location for RWH due to its rainfall pattern as compared with those enjoyed by other universities across SA. Going forward, there is a need for specific data collection on the amount of water used for toilet flushing in each building, detailed design of the RWH systems, and a detailed water quality analysis of harvested rainwater from the various catchments.